Modeling the Strength of MSME Business Connectivity in the Aru Islands District - Karatem, Irma Penina; Sitaniapessy, Rainier Hendrik (Jurnal Ekonomi, 2024)
The strength of business connectivity must be a primary capability for MSMEs in today's highly dynamic conditions. This research model is based on the inconsistency between expert views on the relationship between entrepreneurial orientation and marketing performance and many MSMEs in this area have not been able to improve their business performance properly. To provide a solution, the concept of business connectivity strength was developed which is rooted in the theory of resource advantage. Using a sample of 144 people with the PLS SEM analysis method to test the hypothesis. The results show that all variables have a positive and significant effect. The results of this study provide solutions and implications for future research to strengthen this research model.